Siglec-mediated regulation of immune cell function in disease - Macauley, Matthew S.; Crocker, Paul R.; Paulson, James C. (Nature reviews. Immunology, 2014)
Key Points Siglecs are a family sialic acid-binding immunoglobulin-like co-receptors that are expressed on most cells of the innate and adaptive immune systems. As Siglecs recognize sialic acid-containing glycans that are expressed on all mammalian cells, they can help immune cells to discriminate between self and non-self. Sialylated pathogens can both subvert and promote immune responses through Siglec-dependent interactions. Siglecs have important roles in the regulation of activatory and inhibitory receptors on immune cells, which can influence host–pathogen interactions, inflammation, neurodegeneration, autoimmune diseases and cancer. Most Siglecs exhibit highly restricted expression on immune cell subsets and they are recognized as attractive therapeutic targets for cell type-specific therapies. Siglecs are sialic acid-binding cell-surface proteins that can help the immune system to distinguish between self and non-self. In this Review, the authors describe how Siglecs can modulate immune cell signalling, outline the role of Siglecs in disease and discuss targeting Siglecs for therapeutic purposes. All mammalian cells display a diverse array of glycan structures that differ from those that are found on microbial pathogens. Siglecs are a family of sialic acid-binding immunoglobulin-like receptors that participate in the discrimination between self and non-self, and that regulate the function of cells in the innate and adaptive immune systems through the recognition of their glycan ligands. In this Review, we describe the recent advances in our understanding of the roles of Siglecs in the regulation of immune cell function in infectious diseases, inflammation, neurodegeneration, autoimmune diseases and cancer.